2023
DOI: 10.1186/s12884-023-05639-w
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy- and lactation-induced osteoporosis: a social-media-based survey

Abstract: Background Pregnancy- and lactation-induced osteoporosis (PLO) presenting as spinal fractures is rare, and the spectrum of clinical presentation, risk factors and pathophysiology are incompletely understood. The aim of this study was to delineate clinical parameters, risk factors and osteoporosis-related quality of life (QOL) of women with PLO. Methods Participants of a social-media (WhatsApp) PLO group and mothers of a parents’ WhatsApp group (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Our results were similar to those of a recent systematic review showing that PLO occurs most frequently in the first 3 months after childbirth [ 14 ], but different with regard to the frequency later than 3 months after childbirth, which was 51.1% (24/47) in our study and 4.9% (4/82) in theirs. A very recent survey of PLO showed that more than one-fifth of vertebral fractures occurred later than 12 weeks after childbirth [ 15 ]. One explanation is that a systematic review investigating case reports and series would easily miss underlying patients in whom the physicians had no interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were similar to those of a recent systematic review showing that PLO occurs most frequently in the first 3 months after childbirth [ 14 ], but different with regard to the frequency later than 3 months after childbirth, which was 51.1% (24/47) in our study and 4.9% (4/82) in theirs. A very recent survey of PLO showed that more than one-fifth of vertebral fractures occurred later than 12 weeks after childbirth [ 15 ]. One explanation is that a systematic review investigating case reports and series would easily miss underlying patients in whom the physicians had no interest.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral fractures during the late pregnancy and early postpartum periods have been the most typically described outcome of PLO, although other fractures are possible [ 9 , 12 , 13 ]. Nevertheless, a recent systematic review, as well as a recent social media survey of PLO, investigated only vertebral fractures [ 14 , 15 ]. In Japan, a few epidemiological studies of osteoporosis in young women have recently been published [ 13 , 16 ], but it is difficult to identify the occurrence of fragility fractures without major trauma in large populations with high anonymity.…”
Section: Introductionmentioning
confidence: 99%